Pediatric Plastic Bronchitis: Case Report and Retrospective Comparative Analysis of Epidemiology and Pathology. (11th April 2013) - Kunder, Rebecca; Kunder, Christian; Sun, Heather Y.; Berry, Gerald; Messner, Anna; Frankovich, Jennifer; Roth, Stephen; Mark, John
Abstract : Plastic bronchitis (PB) is a pathologic condition in which airway casts develop in the tracheobronchial tree causing airway obstruction. There is no standard treatment strategy for this uncommon condition. We report an index patient treated using an emerging multimodal strategy of directly instilled and inhaled tissue plasminogen activator (t-PA) as well as 13 other cases of PB at our institution between 2000 and 2012. The majority of cases (n = 8 ) occurred in patients with congenital heart disease. Clinical presentations, treatments used, histopathology of the casts, and patient outcomes are reviewed. Further discussion is focused on the epidemiology of plastic bronchitis and a systematic approach to the histologic classification of casts. Comorbid conditions identified in this study included congenital heart disease (8), pneumonia (3), and asthma (2). Our institutional prevalence rate was 6.8 per 100, 000 patients, and our case fatality rate was 7%.